Community Service Activities: Appreciating Jamu Through the Kindergartens Togetherness - Kartika Nuringsih; Edalmen Edalmen; Harry Kristanto (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2025)
Jamu is known as a herbal product that has benefits for maintaining body stamina. Jamu is synonymous with Javanese tradition, but nowadays the term is generalized to represent herbal drinks. To foster interest in drinking herbal medicine, the dissemination and practice of herbal medicine such as kunyit asam and beras kencur were conducted. The activity was carried out with students, principals, and accompanying teachers at Raudhatul Athfal Taufiqurrahman in Beji Timur Village, Depok. The approach used is Participatory Action Research, which involves the role of teachers and jamu traders during the activity. This activity involved Budhe Sumi as a jamu maker who often sells her jamu around the school. In addition to getting to know various types of jamu, children are introduced to raw materials or empon-empon such as turmeric, kencur, ginger, lemongrass, tamarind, and others. They were given information on how to make jamu and the benefits of jamu in keeping fit. Each child received a 1/4 liter bottle of beras kencur produced by Budhe Sumi, which is useful for relieving coughs, increasing appetite, and relieving fatigue. The results showed that the students recognized kunyit asam and beras kencur. They can taste the flavor and aroma of ginger, turmeric, kencur, lemongrass, and other ingredients. This event provides new experiences for children. The majority of children are interested, even though there are 25 percent of participants who do not like to drink the jamu. It is basic knowledge about jamu in a simple way. This is social engineering to educate children about local cultural wisdom so that the togetherness of stakeholders is very useful to foster caring behavior with local wisdom or pro-local culture behavior.